2023
DOI: 10.1002/hsr2.1603
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology, transmission and clinical features of 2022‐mpox outbreak: A systematic review

Nadim Sharif,
Nazmul Sharif,
Khalid J. Alzahrani
et al.

Abstract: Background and AimsThe 2022‐mpox outbreak has spread worldwide in a short time. Integrated knowledge of the epidemiology, clinical characteristics, and transmission of mpox are limited. This systematic review of peer‐reviewed articles and gray literature was conducted to shed light on the epidemiology, clinical features, and transmission of 2022‐mpox outbreak.MethodsWe identified 45 peer‐reviewed manuscripts for data analysis. The standards of the Preferred Reporting Items for Systematic Review and Meta‐Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Case fatality rate of patients co-infected with mpox-HIV was higher than patients with mpox alone. Previous case series analysis in 2017 in Nigeria [ 22 ] have also found higher case fatality rate among the HIV co-infected cohort. We have also found reports of bacterial secondary infection in the genitals of mpox-HIV co-infected patients, which resulted in hospitalization and prolonged illness in this 2022 outbreak [ 10 ].…”
Section: Epidemiology Of 2022 Mpox Outbreakmentioning
confidence: 87%
See 1 more Smart Citation
“…Case fatality rate of patients co-infected with mpox-HIV was higher than patients with mpox alone. Previous case series analysis in 2017 in Nigeria [ 22 ] have also found higher case fatality rate among the HIV co-infected cohort. We have also found reports of bacterial secondary infection in the genitals of mpox-HIV co-infected patients, which resulted in hospitalization and prolonged illness in this 2022 outbreak [ 10 ].…”
Section: Epidemiology Of 2022 Mpox Outbreakmentioning
confidence: 87%
“…The characteristics muco-cutaneous lesions of mpox have been most frequently isolated from the genitals, anogenital and perineal areas than other organs of the body, which was higher in face, arms, and legs in previous outbreaks [ 2 , [4] , [5] , [6] , [7] , [9] , [10] , [11] , 21 , 16 , 17 ]. Recent studies have reported higher prevalence (54–100 %) and concentration of mpox DNA in semen sample of the infected men [ 7 , 9 , 11 , [13] , [21] , [14] , [20] , [15] , [16] , [17] , [18] , [19] , [22] ]. Several studies have found that isolated DNA of mpox from the lesions of anogenital skin and semen have capability to infect cell lines like Vero E6 cells and produce cytopathic effects [ 12 , 13 ].…”
Section: Epidemiology Of 2022 Mpox Outbreakmentioning
confidence: 99%
“…In this WHO report published on 22 December 2023, a total of 2024 cases were reported, including one death since September 2022 for the first imported case in China [ 3 ]. The MPXV, which can be transmitted through sexual intercourse and direct contacting lesions, saliva, aerosols, as well as contaminated fomite [ 4 ], might cause an epidemic. The symptoms of infections caused by MPXV vary from mild to severe, including skin lesions, lymphadenectasis, fever, vomiting, sepsis, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms of infections caused by MPXV vary from mild to severe, including skin lesions, lymphadenectasis, fever, vomiting, sepsis, etc. [ 1 , 4 ]. The MPXV, a large double-stranded DNA virus (about 197 kb), belongs to the genus of orthopoxvirus of the Poxviridae family, along with three other viruses: variola virus (VARV), cowpox virus (CPXV), and vaccinia virus (VACV).…”
Section: Introductionmentioning
confidence: 99%
“…Mpox symptoms during the 2022 global outbreak are well characterized from large cohorts . Our manual data abstraction process included over 50 fields related to clinical course with coding guidelines for each field, which optimized collection of data, such as symptom onset date.…”
mentioning
confidence: 99%